Substance Abuse and Oral Health of Adolescence - Osadolor, Obehi O; Onyejaka, Nneka K (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Substance abuse is a rising health trend that affects countries worldwide.It is associated with financial, social, medical, oral and economic effects that can affect the user, community and the society. Some substances have been used in the history of mankind for religious, cultural, recreational and medicinal purposes. Substance abuse among adolescents is increasing with possible associated factors like peer influence, availability and affordability of substances, favourable parental attitude to substance use, parental substance use problems, parental approval of substance use in early adolescence, family structure, locality of residence, social bonding, boredom, type of school, and adventurous personality. Oral health conditions among substance abusers may be attributed to the direct impact of the chemical qualities and nature of the illicit substances on oral tissues, decreased saliva production, concentration, personal preference, the frequency and amount of consumption of the abused substanceand the substance abuser associated oral health risk behaviours.